Verification of the Cepheid Xpert Carba-R assay for the detection of carbapenemase genes in bacterial isolates cultured on alternative solid culture media. Issue 3 (November 2017) - Tanner, H.
Summary: The Xpert Carba-R (Cepheid) is a polymerase chain reaction (PCR) assay for detection and differentiation of five common carbapenemase genes. If used according to manufacturer's instructions, bacterial isolates tested must be cultured on blood or MacConkey agar. This study confirms that the assay performs well against a diverse panel of bacterial isolates with known carbapenemase genes. It also demonstrates that the assay performs well using three solid agar culture media that have not been recommended by the PCR assay's manufacturer: CLED (cystine-, lactose-, and electrolyte-deficient), ChromID CARBA-SMART, and a nutrient slope. By testing isolates directly from any of these media, delays in laboratory reporting can be avoided.